SPECIFICATIONS OF SOCIAL MYTH FORMATION IN MODERN SOCIETY - Կեսոյան Հ. Ա. (Արդի հոգեբանություն, 2018)
The article focuses on the study of contemporary social myths, their identification and detection of their applied purposes. We also touched upon the technological solutions used during the "Velvet Revolution" that took place this year in Armenia, the strategic use of which is the basis for the reconstruction of social reality and the formation of modern myths.